A Usability Analysis on the Development of Caregiver Assessment Using Serious Gaming Technology (CAST) Version 2.0: A Research Update. Issue 1 (14th December 2020) - Hughes, Jennifer C.; Evans, JoAnna; Goodman, Garrett; Oliver, Alexandrea; Banerjee, Tanvi; Hughes, John G.; Lawhorne, Larry
Abstract: The COVID-19 pandemic has increased isolation of caregivers making the development of an in-home assessment tool timely. This study examined the usability of the Caregiver Assessment using Serious Gaming Technology (CAST) version 2.0, an application that assesses task performance and stress in dementia caregivers. Following a demonstration on the CAST app, five representative user participants compared versions 1.0 to 2.0, and five participants, also representative users, evaluated version 2.0. Participants provided recommendations for substantive changes including: a reminder feature addition, addition of incentives, updates on appearance and ease of use, and updating the word scramble game (the most significant finding of this usability study). All participants reported their experiences and provided recommendations for further enhancements during semi-structured interviews with social work researchers. Results indicated that the modifications had considerably improved the application's usability. Changes in readability and use were encouraging for future use although continued development of additional games for the app is crucial for ongoing development.